It's all your fault - Rudnick, Paul (Scholastic Press, 2016)
Seventeen-year-old Caitlin Singleberry is a proper Christian teenager and member of a family singing group, but today she has been given a truly impossible assignment...keep her cousin Heller Harrigan, Hollywood wild child, out of trouble for the last weekend before her first big movie debuts
Keywords: Humorous fiction; Cousins -- Juvenile fiction; Teenage actors -- Juvenile fiction; Motion picture actors and actresses -- Juvenile fiction; Singers -- Juvenile fiction; Humorous stories; Cousins; Actors and actresses; Singers; Jugendbuch